Penilaian Potensi Penawaran Wisata Alam Hutan Mangrove Di Tanjung Ngalo, Tapalang Barat, Sulawesi Barat - Ritabulan; Nurhasana; Suparjo Razasli Carong (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
Mangroves are a community or individual plant species forming a tidal area community. One of the stretches of the mangrove ecosystem in West Tapalang District is in Tanjung Ngalo, Dungkait Village. Tanjung Ngalo is one of the tourist attractions in West Tapalang District, Mamuju Regency. However, its location is quite remote with minimal access, which is a challenge for the future development of this area. This research aims to identify and calculate the potential value of mangrove natural tourism offerings in Tanjung Ngalo. Data collection methods were carried out through observation, interviews and literature review. Data analysis used a scoring technique based on the Guidelines for Analysis of Operational Areas of Natural Tourist Attraction Objects (ADO-ODTWA) of the Directorate General of Forest Protection and Nature Conservation Year 2003. The results show that the potential value of the mangrove natural tourism offerings in Tanjung Ngalo is 2,360, included in the medium classification. The accommodation aspect has the lowest potential value (90) so it needs attention for future improvement and development. Keywords: Tanjung Ngalo, mangrove, nature tourism, ADO-ODTWA, supply